An integrative approach to early childhood and Initial Education aactivities within the Basic Education curriculum (Educational Knowledge, 2023)
This study explores the integration of early childhood and initial education activities into the learning process of children in basic education, with a focus on the Language subject. The disconnection between learning processes in early childhood education and basic education is evident, potentially due to differing pedagogical practices. This research employs an action-research approach, observing and analyzing pedagogical practices related to early childhood and initial education activities. Based on identified pedagogical needs, a didactic proposal is designed, emphasizing continuous teacher development through a semi-structured survey that incorporates play, art, literature, and environmental exploration. This approach aims to engage teachers and students with the curriculum and their surroundings.
Keywords: Curriculum; pedagogy; early education; basic education; language